Current Status of Liver Allocation in the United States - Elwir, Saleh (Gastroenterol Hepatol (N Y), 2016)
The liver transplant allocation system is currently based upon the Model for End-Stage Liver Disease (MELD) score and allocates organs preferentially to patients with the highest scores (ie, the sickest patients) within a defined geographic unit. In addition, certain patient populations, such as patients with hepatocellular carcinoma and portopulmonary hypertension, receive MELD exception points to account for their increased waitlist mortality, which is not reflected by their MELD score. Significant geographic variation in the access to liver transplantation exists throughout the United States. Both the Organ Procurement and Transplant Network Board of Directors and the Health Resources and Services Administration have determined these geographic disparities to be unacceptable. The liver transplant community has worked to develop methods to reduce these geographic disparities and to reexamine how MELD exception points are granted to certain patient populations. As a result, numerous policy changes have been adopted throughout the years that have broadened the sharing of organs through wider geographic sharing. Despite all of these changes, variation in access to liver transplantation continues to exist, and, thus, the liver transplant community continues to examine new ways to address geographic disparities. This paper reviews several of the key changes to the liver allocation system that have occurred since the implementation of MELD allocation in 2002 and provides an overview of potential changes to the system.